2013
DOI: 10.1039/c2ta01565j
|View full text |Cite
|
Sign up to set email alerts
|

Modulated formation of metal-organic frameworks by oriented growth over mesoporous silica

Abstract: Engineering the structure of metal-organic frameworks at the molecular level is of major interest for taking MOFs beyond their uses as bulk materials and creating multifunctional features with advanced applications. The notion involves directing MOF structure and controlling crystallization in terms of phase and orientation through interactions with directing agents. We have successfully used different concentrations of SBA-15 mesoporous silica for directed growth of the archetypal MOF-5 microcrystals along pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 63 publications
(92 reference statements)
0
29
0
Order By: Relevance
“…In addition, UiO-66 particles in UiO-66-CNT sample seemed to be slightly larger than pristine UiO-66 and UiO-66-NH2. It has been reported that the existence of external component could alter the growth direction and size (Karimi and Morsali, 2013). The larger UiO-66 particles might be due to the suspended CNTs in DMF, which affected the growth of UiO-66.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, UiO-66 particles in UiO-66-CNT sample seemed to be slightly larger than pristine UiO-66 and UiO-66-NH2. It has been reported that the existence of external component could alter the growth direction and size (Karimi and Morsali, 2013). The larger UiO-66 particles might be due to the suspended CNTs in DMF, which affected the growth of UiO-66.…”
Section: Resultsmentioning
confidence: 99%
“…Though a microporous MOF was chosen as demonstration, it shows greater promises for the future development of mesoporous MOFs with 2D morphologies, for their relatively larger pore sizes often make it harder to elaborately control the orientation of the framework crystallization. Similarly, modulated formation of oriented growth over mesoporous silica has also been conducted . Karimi et al used different concentrations of SBA‐15 mesoporous silica for the formation and growth of the MOF‐5 microcrystals along specific orientations, which leads to the samples of flower‐like or nanorod structures rather than a cubic one.…”
Section: Fabrication Strategies To Mesoporositymentioning
confidence: 99%
“…k) TEM images of MS/2, m) the SBA‐15 in MS/2 composite, and n) MS/3. Reproduced with permission . Copyright 2013, The Royal Society of Chemistry.…”
Section: Fabrication Strategies To Mesoporositymentioning
confidence: 99%
“…[49][50][51] The other method is direct insertion of presynthesized nanoparticles such as metal, metal oxide, POMs, organic polymers, carbon-based materials, SiO 2 into MOF pores or mixing nanoparticles into MOF precursors by solvothermal synthesis, making MOF materials around the nanoparticles. [52][53][54][55][56][57][58] In the latter method, the nanoparticles are usually decorated with suitable surface functional groups which can enhance the combination of nanoparticles and MOFs. [59] For MOFs acting as functional species, direct dispersion of MOF nanoparticles within the meso-/macroporous materials such as polymers, carbon-based materials and SiO 2 , and immersion of meso-/macroporous materials in MOF precursors under solvothermal synthesis are all effective strategies to construct MOF composites.…”
Section: Figurementioning
confidence: 99%